ANALYSIS OF STUDENT RESPONSES TOWARDS THE IMPLEMENTATION OF STEM-BASED COOPERATIVE LEARNING IN SCIENCE EDUCATION - Pratiwi, Dwi Setyo; Salam, Ahmad Abdun (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
The development of 21st-century skills such as critical thinking, collaboration, and problem-solving requires innovative learning approaches. STEM education, integrated with cooperative learning, is considered an effective strategy to enhance student engagement and understanding in science education. This study aims to analyze student responses to the implementation of STEM-based cooperative learning in science education. The research employed a descriptive quantitative approach using a survey method. A total of 31 junior high school students participated by completing a Likert-scale questionnaire consisting of ten statements. The results showed that students responded very positively, with an average score of 81.21%. The findings indicate that this learning approach enhances students' confidence in asking questions and expressing opinions, minimizes boredom, facilitates problem-solving, and improves understanding of the material. It is concluded that STEM-based cooperative learning is an effective and engaging strategy for science education. Further research is recommended to explore its long-term impact on academic achievement and to apply the approach across different subjects and educational levels.